2008
DOI: 10.1007/s10562-008-9586-2
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch Synthesis Using Zeolite-supported Iron Catalysts for the Production of Light Hydrocarbons

Abstract: Fischer-Tropsch synthesis (FTS) for the production of olefins from syngas was investigated on FeCuK impregnated on zeolite catalysts such as ZSM-5, Mordenite and Beta-zeolite. ZSM-5 supported catalyst showed the best activity among the three catalysts due to the high reducibility of iron oxides. It also exhibited high olefin selectivity compared to a catalyst prepared by physical mixing of the two components, due to the presence of moderate number of acid sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 27 publications
(27 reference statements)
4
52
0
Order By: Relevance
“…Similarly, a recent study by Kang et al showed that, although an impregnated catalyst Fe/Cu/K/ZSM-5 had a slightly lower CO conversion with respect to one prepared by physical mixing of the two components, the former exhibited a higher affinity and thus produced more olefins (Figure 3). [130] In addition, the initial conversion was very low on physically mixed catalysts and showed an increasing trend with time-on-stream compared to the impregnated catalyst, which displayed a much higher initial activity (Figure 2). These effects are attributable to the different dispersion of the active phase caused by the preparative methods.…”
Section: Methods Of Catalyst Preparation: Synthesis and Pretreatmentsmentioning
confidence: 95%
See 4 more Smart Citations
“…Similarly, a recent study by Kang et al showed that, although an impregnated catalyst Fe/Cu/K/ZSM-5 had a slightly lower CO conversion with respect to one prepared by physical mixing of the two components, the former exhibited a higher affinity and thus produced more olefins (Figure 3). [130] In addition, the initial conversion was very low on physically mixed catalysts and showed an increasing trend with time-on-stream compared to the impregnated catalyst, which displayed a much higher initial activity (Figure 2). These effects are attributable to the different dispersion of the active phase caused by the preparative methods.…”
Section: Methods Of Catalyst Preparation: Synthesis and Pretreatmentsmentioning
confidence: 95%
“…Various methods have been used to introduce iron, such as the addition of the metal precursor into the synthesis gel, [129,135] ion exchange, [131,136] impregnation, [114,130] vapor phase deposition, [101] or physical mixing of the zeolite with the iron precursor [102][103][104]127] or iron catalyst. [120] The catalytic performance of the resulting catalysts strongly depends on the prep- aration method, resulting in iron species located at considerably different positions in the support.…”
Section: Methods Of Catalyst Preparation: Synthesis and Pretreatmentsmentioning
confidence: 99%
See 3 more Smart Citations